Practical behaviour management solutions for children and teens with autism : the 5P approach - Miller, Linda (Linda Janice) (Jessica Kingsley Publishers, 2010)
Children and young people with autistic spectrum disorders present many challenges to the people who care for them. 'Difficult' or challenging behaviour is often encountered on a daily basis, and it is easy for both parents and professionals to feel completely overwhelmed by its sheer range and complexity. Where do you start? What happens when, in managing one set of problems, another gets worse? Is there some way to tackle difficulties before they get out of hand, or even before they arise?. Practical Behaviour Management Solutions for Children and Teens with Autism answers these questions an.